2015
DOI: 10.1007/s00127-015-1164-5
|View full text |Cite
|
Sign up to set email alerts
|

Secondhand smoke exposure and mental health in adults: a meta-analysis of cross-sectional studies

Abstract: Exposure to SHS among non-smoker is associated with depressive symptoms and psychological distress, emphasizing the significance of reducing SHS exposure at a population level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
16
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 55 publications
4
16
0
2
Order By: Relevance
“…While some studies have found no association between tobacco use and STS (Craun & Bourke ), other studies have shown that nicotine has anxiolytic effects that may alleviate some symptoms of anxiety and traumatic stress (Kutlu et al ; Morissette et al ). Conversely, since recent studies have demonstrated that second‐hand tobacco smoke exposure is associated with addictive behaviours and psychological distress (Okoli ; Zeng & Li ), greater second‐hand tobacco smoke exposure may increase a person's vulnerability to STS, but this association is merely speculative at this point. In addition, having a history of a behavioural health problem and recent alcohol use were variables also associated with BO, as has been found in other studies (Creedy et al ; Guo et al ; Rath et al ).…”
Section: Discussionmentioning
confidence: 99%
“…While some studies have found no association between tobacco use and STS (Craun & Bourke ), other studies have shown that nicotine has anxiolytic effects that may alleviate some symptoms of anxiety and traumatic stress (Kutlu et al ; Morissette et al ). Conversely, since recent studies have demonstrated that second‐hand tobacco smoke exposure is associated with addictive behaviours and psychological distress (Okoli ; Zeng & Li ), greater second‐hand tobacco smoke exposure may increase a person's vulnerability to STS, but this association is merely speculative at this point. In addition, having a history of a behavioural health problem and recent alcohol use were variables also associated with BO, as has been found in other studies (Creedy et al ; Guo et al ; Rath et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiology evidence about the relation between SHS exposure and depressive symptoms has been reported mainly among adults [ 14 , 15 , 16 , 17 , 18 , 19 ], and current evidence is inconsistent. A few studies have demonstrated significant relations [ 14 , 15 , 16 , 17 , 18 ], while a nonsignificant relation was found in another report [ 19 ]. Compared to the number of studies on adults, few studies report on this relation in adolescents [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the potential relationship between SHS exposure and depressive disorders has not been well established. Although there is increasing evidence for this association, the current findings are inconsistent [13,14,15,16,17,18,19,20]. For example, SHS exposure was significantly associated with increased risk of depressive symptoms in some studies [15,16], but non-significant relations were observed in other studies [14].…”
Section: Introductionmentioning
confidence: 94%